Point mutation in Kit receptor tyrosine kinase reveals essential roles for Kit signaling in spermatogenesis and oogenesis without affecting other Kit responses - Kissel, Holger (Oxford University Press, 2000)
The Kit receptor tyrosine kinase functions in hemato– poiesis, melanogenesis and gametogenesis. Kit receptor-mediated cellular responses include proliferation, survival, adhesion, secretion and differentiation. In mast cells, Kit-mediated recruitment and activation of phosphatidylinositol 3′–kinase (PI 3–kinase) produces phosphatidylinositol 3′–phosphates, plays a critical role in mediating cell adhesion and secretion and has contributory roles in mediating cell survival and proliferation. To investigate the consequences in vivo of blocking Kit-mediated PI 3–kinase activation we have mutated the binding site for the p85 subunit of PI 3–kinase in the Kit gene, using a knock-in strategy. Mutant mice have no pigment deficiency or impairment of steady-state hematopoiesis. However, gametogenesis is affected in several ways and tissue mast cell numbers are affected differentially. While primordial germ cells during embryonic development are not affected, Kit(Y719F)/Kit(Y719F) males are sterile due to a block at the premeiotic stages in spermatogenesis. Furthermore, adult males develop Leydig cell hyperplasia. The Leydig cell hyperplasia implies a role for Kit in Leydig cell differentiation and/or steroido– genesis. In mutant females follicle development is impaired at the cuboidal stages resulting in reduced fertility. Also, adult mutant females develop ovarian cysts and ovarian tubular hyperplasia. Therefore, a block in Kit receptor-mediated PI 3–kinase signaling may be compensated for in hematopoiesis, melano– genesis and primordial germ cell development, but is critical in spermatogenesis and oogenesis.